Ferramenta Móvel para a realização de inquéritos de satisfação - Luís Miguel Gonçalves (2017)
The use of product satisfaction tools plays an important role for companies in this day and age of high competition, helping them define strategies and raising a whole new spectrum of users. One of the oldest, but still most meaningful type of market study methods is face-to-face surveys. In order to get a significant sample, a large number of this type of inquiries is required, which demands inquirers to go through the same process multiple times, making the task very time consuming. Moreover, the error factor in the integration and treatment of collected information is an issue that handwritten survey answers often deal with. The aim of this project is to define and develop a tool that can be installed on a tablet device and used by field agents to easily and effectively perform face-to-face surveys. By focusing and studying, alongside both field agents and the people responsible for data treatment and analysis, the goal is to further understand their current hardships and needs, in order to minimize the informational retrieval time and errors. This is to be achieved by following the Google Material Design guidelines, such as typography, grids, space, scale and colour to create hierarchy and meaning that allows the user to navigate, understand, and use the user interface successfully without much previous training. There are already generic platforms for conducting surveys, however the tool is to be adaptable and simple enough to be used in different contexts in order to maximize its investment. The end goal is to have a platform capable of adapting to the specific context of the transport world, allowing the registration of surveys even when web access is non-existent and their subsequent integration into a data format that can be used by statistical treatment tools. As a result of this work, it should be possible for any individual, previously trained, to swiftly design a survey via the computer application and have it be generated on to a tablet in a survey format. The mobile application should be prepared to address the intricacies of face-to-face surveys and the computer application simple yet complete with all the needed tools for creating an assortment of surveys. Both applications are to be developed during the course of this dissertation.